PENGARUH KEWAJIBAN E-SPT MASA PPN TERHADAP EFISIENSI PEMROSESAN DATA PERPAJAKAN - Sari, Yuanita Kartika (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The effort of modernism system of the process taxation data is being done frequently. One of the effortsis Regulation Number 11/PJ/2013 which is compulsory the Taxable business people to use e-SPT. Thisobservation has purpose to find out the perception, obligation influence and e-SPT application to the tax dataprocessing efficiently. This observation object was businessman included tax that registered in Primary TaxService Office of Surabaya (Genteng). The research result shows that obligation and e-SPT application on PPNprocess has significant influence to the tax data processing because the obligation of e-SPT encourage taxpayermore efficient processing taxation by using application that supports achievement of efficiency that producesquality information, low costs, save time and minimize performance of Human Resources. Whereas theperception of socialization and orientation has compulsory purpose of e-SPT included good category, while thetimeliness within enough category. Perceptions of e-SPT application in terms of safety, practicality, ease of use,ease of recording of data, ease of reporting and ease of upgrades and updates go in either category. Aboutperceptions taxation data processing efficiency in terms of output, the cost, time and performance of HumanResources in either category.Keywords: Obligation, e-SPT application, efficienctly.